Court Assistance in the Taking of Evidence in International Arbitration Dissertation - Raess, Lorenz (sui generis Verlag, 2020)
Although international arbitration is widely hailed as an efficient, confidential and flexible way of settling commercial disputes, it has its limits. The arbitral tribunal's lack of coercive power is thrown into particularly stark relief when it comes to the taking of evidence from third parties outside the arbitral proceedings. If they do not comply voluntarily with the request of the arbitral tribunal to testify as a witness or disclose documents, assistance must be sought from state courts. As the success of a case hinges on the evidence that a party can obtain, it is crucial to understand how to obtain evidence through state courts. At the heart of this work is the question of the conditions under which state courts may offer assistance in international arbitral proceedings. With a special focus on Switzerland and comparative aspects, this book provides helpful tactical insights for arbitral practitioners around the world.